The effect of a novel movement strategy in decreasing ACL risk factors in female adolescent soccer players - Celebrini, R. G.; Eng, J. J.; Miller, W. C.; Ekegren, C. L. (The Journal of Strength and Conditioning Research, 2012)
There is a need to investigate the effect of specific movement strategies in reducing biomechanical risk factors for anterior cruciate ligament injury in young female athletes. The purpose of this study was (a) to determine the feasibility of implementing a novel movement strategy (Core-PAC) into a team warm-up before soccer training based on subject compliance and integration of the Core-PAC into the warm-up and (b) to determine whether the Core-PAC would improve peak knee flexion angles and peak abduction moments at the knee during a side cut (SC) and an unanticipated side cut (USC) before kicking a soccer ball, and a side hop (SH) task after immediate instruction and after a 4-week training program. A convenience sample of ten 14- to 16-year-old female soccer players were instructed in the Core-PAC immediately after baseline testing and during a training program consisting of a 20-minute warm-up, 2 times per week. The Core-PAC was understood and accepted by the subjects and incorporated into their warm-up activities with good compliance. After the immediate instruction, there were significant increases in peak knee flexion angles of a mean 6.4° during the SC (p = 0.001), 3.5° during the USC (p = 0.007), and 5.8° during the SH (p < 0.001) tasks. Peak knee abduction moments decreased by a mean of 0.25 N·m/kg during the SC (p < 0.03), 0.17 N·m/kg during the USC (p = 0.05), and 0.27 N·m/kg during the SH (p = 0.04) tasks. After the 4-week training program, some individuals showed improvement. The results of this study suggest that the Core-PAC may be 1 method of modifying high-risk movements for ACL injury such as side cutting and single-leg landing.